Multivariate sea storm hindcasting and design: the isotropic buoy-ungauged generator procedure - Gianfausto Salvadori (Nature Portfolio, 2020)
Abstract The present work provides indications for assessment of wave climate and design of structures at sea at ungauged sites, both critical issues in Ocean sciences. The paper is of methodological nature and of global worldwide applicability. It shows how suitable wave hindcasting relations can be exploited in order to provide sea storm scenarios at an ungauged (Target) location useful for design purposes: in particular, only geographical information and the knowledge of another gauged (Source) buoy are used. Several are the novelties introduced. (i) New hindcasting relations are derived. (ii) A full statistical model is set up for the Target area, whereas traditional hindcasting simply transfers time series from a gauged to an ungauged site: this gives the possibility to appropriately deal with design and hazard assessment at the Target location. (iii) The multivariate behavior of non-independent random variables is properly modelled by using the Theory of Copulas. As an illustration, a number of case studies is investigated, involving four pairs of buoys which, given their positions and exposures, are representative of a wide variety of sea states and conditions, as well as of different wave generation mechanisms.